Pengembangan modul mahir ejaan bahasa indonesia berbasis kearifan lokal untuk siswa sekolah dasar - Agung Priyono (COLLASE (Creative of Learning Students Elementary Education), 2023)
This study aims to design the MEBI (Mahir Spelling Indonesian) module based on local wisdom in Rembang Regency as an alternative learning resource for sixth grade elementary school students. The R&D research method on Sugiyono's theory was modified in seven research steps, namely: 1) potential and problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, 6) product trial, and 7) revision. product. Data collection techniques were carried out through observation and questionnaires. Observations during the preliminary study, while the data from expert validation and student responses were obtained from an assessment questionnaire with a Likert scale. The design of the MEBI module development begins with analyzing the material that aims to help students find the contents of the book according to their needs, namely alternative learning resources for editing materials for words/terms, phrases, sentences, paragraphs, spelling, and punctuation. The MEBI module consists of five discussion materials, namely about PUEBI, the use of capital letters, punctuation marks, prepositions, and standard words and effective sentences. Each subject is equipped with Let's Practice which encourages students to think actively and Come on Testing Ability which gives students the opportunity to measure learning achievement. The MEBI module is equipped with attractive illustrations and delivered in communicative language by the two main characters, namely Azzam and Diva. The MEBI module is printed in the form of a book with a size of 25 cm x 17.5 cm. In addition, the MEBI module is also made in the form of a flipbook application that can be operated on an Android-based smartphone. This means that the MEBI Module can be used anywhere and anytime. The conclusion of this research is the MEBI (Mahir Spelling Indonesian) Module Design in the form of printed books and flipbook applications that can be operated on Android smartphones.Keywords: Local Wisdom, Spelling Module, Elementary School